Job burnout and anxiety among medical staff: A latent profile and moderated mediation analysis - Hao, Shuwei; Zhang, Xueting (Social science & medicine (1982), 2024)
Due to work pressure, work intensity, and the impact of emergencies such as the epidemic, job burnout and mental health problems among medical staff have become increasingly prominent. Our study aims to characterize the patterns of burnout in Chinese medical staff, explore the profile differences on anxiety and self-esteem, examine whether the differences in these profiles on anxiety were mediated by self-esteem, and investigate whether this mediating process was moderated by positive coping styles among medical staff. Data were collected from 602 medical staff in China by a convenient sampling method. A latent profile and moderated mediation analysis were performed. Latent profile analysis on three burnout dimensions [emotional exhaustion, cynicism, and professional efficacy] indicated two burnout profiles: low burnout (82.47% of the sample) and high burnout (17.53%). Medical staff with a low burnout profile had lower levels of emotional exhaustion and cynicism than those with a high burnout profile. It was also determined that self-esteem mediates burnout and anxiety in both high- and low-burnout medical staff. The moderating role of positive coping styles was also identified (β = 0.30, 95%CI: 0.058–0.550). The identification of two distinct burnout patterns (low burnout and high burnout) provides clinical administrators with clear goals for individualizing support and interventions for medical staff with different levels of burnout. Furthermore, attention should be given to self-esteem and positive coping styles, as they act as potential mediators and moderators of medical staff's mental health problems. •The job burnout of medical staff could be divided into two profiles: high and low.•Self-esteem partially mediated the relationship between burnout and anxiety of medical staff.•PCS was a moderator between self-esteem and anxiety for medical staff with high burnout.